A framework for using rough sets and formal concept analysis in case based reasoning - Tadrat, Jirapond; Boonjing, Veera; Pattaraintakorn, Puntip (My University, 2007)
A significant open problem of case based reasoning system is a construction of better knowledge base. We propose a new framework for constructing alternative knowledge base in case based reasoning system based on rough sets and formal concept analysis. Our framework first applies rough set theory for discovering reduced cases required in a case based reasoning system. We then achieve further hierarchical structure of knowledge base using formal concept analysis. The result is the concept lattice knowledge base embedded to our proposed case based reasoning system. A part of case based reasoning system is developed with an example throughout. We also discuss how our proposed framework can be beneficial for a case based reasoning system. © 2007 IEEE.